Cognitive Impairment in MASLD is associated with Amygdala-Related Connectivity Dysfunction in the Prefrontal and Sensory Cortex - Yihan Jin; Ruoyu Tang; Liqiang Wu; Kuanghui Xu; Xiaofei Chen; Yaxin Zhu; Junping Shi; Jie Li (Journal of Integrative Neuroscience)
Background: Metabolic dysfunction-associated steatotic liver disease (MASLD) is a common metabolism-related multisystem clinical disorder, often accompanied by a high comorbidity of mild cognitive impairment (MCI). Increasing evidence suggests that the amygdala is crucial in cognitive processing during metabolic dysfunction. Nevertheless, the role of the amygdala in the neural mechanisms of MASLD with MCI (MCI_MASLD) remains unclear. Methods: A total of 74 MASLD patients (43 with MCI_MASLD and 31 without MCI [nonMCI_MASLD]) and 62 demographic-matched healthy controls (HC) were enrolled. All participants underwent resting-state functional magnetic resonance imaging scans and psychological scale assessments. Liver fat content and blood index measurements were performed on the patients. Using the bilateral amygdala as seeds, the seed-based functional connectivity (FC) maps were calculated and one-way analysis of covariance with post hoc tests was performed to investigate the difference among the three groups. Results: Compared to nonMCI_MASLD patients, MCI_MASLD patients demonstrated enhanced FC between the right amygdala and the medial prefrontal cortex (mPFC), while reduced FC between the left amygdala and the left supplementary motor area (SMA). Interestingly, the FC values of the mPFC were correlated with the Montreal Cognitive Assessment Scale (MoCA) scores and liver controlled attenuation parameters, and the FC values of the SMA were also correlated with the MoCA scores. Furthermore, the FC values between the bilateral amygdala and regions within the frontal-limbic-mesencephalic circuits were higher in MASLD patients when compared to HC. Conclusions: Aberrant FC of the amygdala can provide potential neuroimaging markers for MCI in MASLD, which is associated with amygdala-related connectivity disturbances in areas related to cognition and sensory processing. Moreover, visceral fat accumulation may exacerbate brain dysfunction.